ANALYSIS OF MUSABAQAH TILAWATIL QUR'AN ACTIVITIES IN INCREASING MOTIVATION FOR MEMORIZING THE QUR'AN IN MADRASAH ALIYAH TAHFIZHIL QUR'AN MEDAN - Nasution, Mawaddah; Addni Annas, Nurjannati (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
In memorizing the Qur'an, motivation is needed, both motivation to add new memorization, motivation to maintain memorization, and discipline motivation to divide time so that the quality and quantity of memorization are maintained properly. However, in reality, many memorizers of the Qur'an still have low motivation, so they have difficulty memorizing the Qur'an. Many want to memorize the Al-Qur'an but are worried that they will not be able to memorize it in the future. Musabaqah Tilawatil Qur'an (MTQ) is an effort to provide motivation to the younger generation to read, memorize and understand the Qur'an. With the existence of Musabaqah Tilawatil Qur'an (MTQ) it becomes a forum to increase motivation to memorize the Al-Qur'an and as a means for memorizers of the Al-Qur'an to test the quality of their memorization. The rapid development of MTQ in Indonesia is a manifestation of people's love for the Qur'an. MHQ in this case is considered to be able to motivate memorizing the Al-Qur'an, so that it is hoped that the students at Madrasah Aliyah Tahfizhil Qur'an Medan have good memorization skills and motivation to memorize. From this research it can be concluded that it can be concluded that the students who memorize the Al-Qur'an at Madrasah Aliyah Tahfizhil Qur'an Medan have their own way of memorizing the Al-Qur'an. This can be seen from their ability to apply self-motivation, self-management and preparation for MTQ.